Effects of ultraviolet radiation as a climate variable on the geographic distribution of Oryza sativa under climate change based on Biomod2 - Wang, Rulin; Guo, Xiang; Song, Yanling; Cai, Yuangang; Wu, Yuhan; Wang, Mingtian (Frontiers in Plant Science, 2025)
IntroductionOryza sativa is one of the most important cereal crops globally.MethodsThe aim of this study was to map areas suitable for the growth and conservation of O. sativa under current and future climatic conditions, and to observe the effects of UV variables on the distribution area of O. sativa.ResultsBased on species distribution records, we used the Biomod2 platform to combine climate data, future shared socioeconomic pathways, and elevation data. The ensemble model (EM) was constructed by screening multiple species distribution models (SDMs), including RF, GBM, ANN, and MARS. The ROC value of the joint model is greater than 0.95, indicating that the model has high reliability and accuracy. Mean annual temperature (bio01), temperature seasonality (bio04), minimum temperature in the coldest month (bio06), mean temperature of coldest quarter (bio11), human footprint and human activity impact index (hfv2geo1) and annual average ultraviolet radiation (uvb1annualmeanuv.b) were the most important environmental variables affecting the suitable distribution area of O. sativa. Under the current climate conditions, the suitable habitats of O. sativa are mainly distributed in the south of the Yangtze River. In the future climate scenario, the total suitable habitat area of O. sativa tended to decrease, but the suitable distribution area under the influence of UV was larger than that without UV.DiscussionClimate change will significantly affect the potential distribution of O. sativa in China and increase its extinction risk. Therefore, it is necessary to provide a reference for the conservation, management, introduction and cultivation of food crops in China.